SPORTS, PHYSICALEDUCATION AND VALUES – FOR NAETHICS IN PHYSICALAND SPORTS ACTIVIES (Fiep Bulletin - online, 2012)
This articles presents a panorama of humankind universal documents and documents in the field ofPhysical Education and Sports, conceived to react several crises that have inflicted this area. The analysis ofthese social-political documents followed by thu understanding of the historical process of PhysicalEducation/Sports leads to the search of and Ethics in the passage from the 20th to the 21st centuries. The mainreference of this Ethics in the invariable is the invariable connection to the prevailing question of everyone's rightsto the physical activies and sports practices, as it was established in the Berlin Agenda at the World Summit onPhysical Education (ICSSPE, 1999) and in the 2000 FIEP Physical Education World Manifesto. The article alsopresents the relationship between the Ethics of Everyone's Rights to Physical Education and the Ethics ofInterdisciplinarity and Social Commitments, understood as Relational Precepts, and the Ethics of Co-Existence,understood here as references the Physical Education and Contemporary Sports must comply with in order tocatch up with the facts in the current historical moment.
Keywords: physical education; sports; ethics; relational precepts